Novel Intervention in the Aging Population: A Primary Meningococcal Vaccine Inducing Protective IgM Responses in Middle-Aged Adults - van der Heiden, Marieke; Boots, Annemieke M. H.; Bonacic Marinovic, Axel A.; de Rond, Lia G. H.; van Maurik, Marjan; Tcherniaeva, Irina; Berbers, Guy A. M.; Buisman, Anne-Marie (Frontiers in Immunology, 2017)
Introduction Vaccine responses are often reduced in the elderly, leaving part of the elderly population vulnerable to infectious diseases. Timely vaccination may offer a solution for strengthening memory immunity before reaching old age, which classifies middle-aged persons as a target age group for vaccine interventions. However, knowledge regarding the immunogenicity of primary immunizations in middle-aged adults is lacking. We determined the immunogenicity of a primary meningococcal vaccine towards which no or (very) low pre-vaccination immunity exists in middle-aged adults (NTR4636). Methods A vaccine containing multiple meningococcal groups (tetravalent) conjugated to tetanus toxoid (MenACWY-TT) was administered to middle-aged adults (50-65 years of age, N= 204) in a phase IV single-center and open-label study. Blood samples were taken pre-, 7 days, 28 days, and 1 year post-vaccination. Functional antibody titers were measured with the serum bactericidal assay (SBA). Meningococcal and tetanus specific antibody responses were determined with a fluorescent bead-based multiplex immunoassay. A bi-exponential decay model was used to estimate long-term protection. Results In the majority of the participants, the meningococcal vaccine clearly induced naïve responses to MenW and MenY as compared to a booster response to MenC. After 28 days, 94%, 99%, and 97% of the participants possessed a protective SBA titer for MenC, MenW and MenY, respectively, which was maintained in 76%, 94%, and 86% one year post-vaccination. At this one year time point, significantly lower SBA titers were found in participants without a pre-vaccination SBA titer. Overall, protective antibody titers were predicted to persist after 10 years in 40-60% of the participants. The SBA titers correlated well with the meningococcal specific IgM responses, especially for MenW and MenY. Interestingly, these IgM responses were negatively correlated with age. Conclusion Primary immunization with a tetravalent meningococcal vaccine was highly immunogenic in middle-aged adults, inducing protective antibody titers in the vast majority of the participants lasting for at least one year. The age-related decrease in highly functional IgM responses argues in favor of vaccination against de novo antigens before reaching old age, and hence middle-aged persons are an age group of interest for future vaccine interventions to protect the aging population.